2019
DOI: 10.18502/jchr.v8i3.1563
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Skin Cancer Preventive Behaviors Based on the Extended Parallel Process Model in Yazd University of Medical Sciences Students, 2017

Abstract: Background: Skin cancer is one of the most common cancers that is mostly caused by ultraviolet radiation. The aim of this study was to investigate the factors affecting skin cancer preventive behaviors in medical sciences students based on the extended parallel process model that is responsible for the future health of the community. Methods: This descriptive cross-sectional study was carried out among 150 students who were selected by the simple random sampling method in Yazd in 2017. The data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Depression and sadness were among other feelings they claimed they would experience. A study that confirmed this finding was conducted by Mazloomy et al among university students, who perceived skin cancer a threat [22]. Another study in American adults showed that when diagnosed with melanoma, people experience a shock, fear, and anxiety.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…Depression and sadness were among other feelings they claimed they would experience. A study that confirmed this finding was conducted by Mazloomy et al among university students, who perceived skin cancer a threat [22]. Another study in American adults showed that when diagnosed with melanoma, people experience a shock, fear, and anxiety.…”
mentioning
confidence: 73%
“…About half of the participants mentioned such issues as the effectiveness of protective measures and the fatality of the disease. In the body of research on the public, skin cancer showed to be perceived as fatal, fearsome, and incurable [20][21][22][23][24]. American farmers also confirmed this finding and reported skin cancer to be deadly [21].…”
mentioning
confidence: 91%
See 1 more Smart Citation